2009
DOI: 10.1177/0731684408100266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Hemp Fiber Polypropylene Composites at Different Operating Temperatures

Abstract: In order to quantify the effect of temperature on the mechanical properties of hemp fiber polypropylene composites, formulations containing 25% and 40% (by weight) hemp fiber were produced and tested at three representative temperatures of 256, 296, and 336 K. Flexural, tensile, and impact tests, as well as dynamic mechanical analysis, were performed and the reduction in mechanical properties were evaluated. Impact resistance was independent of temperature, whereas flexural and tensile properties were strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Polyethylene usually shows three relaxation peaks via DMA, namely α , β , and γ . The γ relaxation corresponds to the glass transition temperature ( T g ) of the polymer and is related to the amorphous phase, while the α relaxation is associated to chain segment mobility in the crystalline phase.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Polyethylene usually shows three relaxation peaks via DMA, namely α , β , and γ . The γ relaxation corresponds to the glass transition temperature ( T g ) of the polymer and is related to the amorphous phase, while the α relaxation is associated to chain segment mobility in the crystalline phase.…”
Section: Resultsmentioning
confidence: 98%
“…The γ relaxation corresponds to the glass transition temperature ( T g ) of the polymer and is related to the amorphous phase, while the α relaxation is associated to chain segment mobility in the crystalline phase. Finally, the β transition corresponds to the mobility of side branches . Previously, it was observed that LMDPE had two major transitions in its loss factor (tan δ ) curves, namely α and γ .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the method of cellulose modification varies the final material properties to different extents. Lower values of storage and loss moduli might evidence the poor filler-polymer matrix interactions [104,105] and, therefore, the low modification yield.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…One of the most common experiments to characterize materials in mechanical properties is the three point bending test [17] . Different polymerization temperatures and fibers volume fraction GF/pCBT composite specimens were manufactured for measuring mechanical strength and the flexural tests according to ASTM-D790 were carried out using Instron 4505 electron universal testing machine at room temperature [18,19] .…”
Section: Mechanical Propertiesmentioning
confidence: 99%